Dança em Bhakti Yoga: vivências de uma bhakti yogi artista pesquisadora e professora na perspectiva da etnocenologia - SILVA, Thelma Verônica Bernardino Mendes da (2023)
The objective of this final paper was to analyze dance in Bhakti Yoga, through my experiences as a Bhakti yogi vaisnava artist-researcher and yoga teacher. As a theoretical and methodological support, I used the studies of Ethnoscenology, according to Pradier (1995) and Bião (1998), in order to base the spectacularity of dance in the Bhakti Yoga Movement, under the epistemological view of spectacular human practices and behaviors. Theorists and researchers such as Valera (2015) and Silveira (2000), who are practitioners of dance in the spiritual context of Bhakti Yoga, Hari Nama Sankirtana and dance in the Vaisnava temple, and contribute to the understanding of eastern cultures, were the bibliographical support. The research approach is qualitative-descriptive and, for this, I bring my experiences and observations of Bhakti Yogi. As a result, I present my experiences in the field of dance, through the research group in Modern Dance, from the Theater and Dance School of the Federal University of Pará, presenting Tunga Vidya Natya Yoga, that is, my look-perceiving-doing on the practice of dance and its connection with the Divine and the sacred. Thus, the experiences reported in dance practices are like a spiritual and artistic path, with regard to both research and artistic production, as well as the preservation of a millenary ancestral knowledge, which is the knowledge of Bhakti Yoga in its essence, the prema bhakti, pure love for Krishna.